PENGARUH CARBON FIBRE SHEET TERHADAP PENINGKATAN KAPASITAS LENTUR PADA BALOK BETON BERTULANG - Mulyadi Mulyadi (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2017)
This research aims to determine the effect of using carbon fiber sheet (cfs) to bending behavior of reinforced concrete beams. The test object that became the object of this research is a reinforced concrete beam with the addition of cfs with size 20 cm x 30 cm x 220 cm. The number of beam test objects is 3 beams and 19 concrete quality control test objects. The test specimen is divided into three types: type I test specimen without reinforcement, type II specimen with 1 layer reinforcement and type III specimen with 2 layer cfs reinforcement. Flexural testing is done by placing a beam on two pedestals with a spacing between 200 cm and then loaded with two centralized loads with the distance between the two loads is 60 cm. The beams are loaded gradually until they reach the peak load. Each load stage recorded the amount of load and tensile reinforcement strain that occurred. The results showed that the addition of cfs can increase the bending capacity. In the case of yield capacity of non-reinforced beam bending, with 1 layer reinforcement and with 2 layer cfs strengthening are 1095 kgm, 2471 kgm and 3892 kgm, respectively. Improved bending capacity of beams with 1 layer reinforcement and with 2 layer cfs reinforcement of cuffs without reinforcing cfs are 126% and 255% respectively. Under ultimate circumstances, the bending capacity of the test specimen without reinforcement, with 1 layer reinforcement and with 2 cylinders reinforcement are 2380 kgm, 3500 kgm and 4655 kgm, respectively. Improved bending capacity of specimens by reinforcing 1 layer and beam with 2 lapiscfs retrofitting of test specimens without reinforcing cfs were 47% and 96% respectively.Keywords: cfs, bending capacity, reinforced concrete beams